FRI0262 Monitoring disease activity in systemic lupus erythematosus with digital elisa quantification of serum interferon-Α. (12th June 2018) - Mouries-Martin, S.; Mathian, A.; Dorgham, K.; Devilliers, H.; Cohen-Aubart, F.; Garrido Castillo, L.N.; Haroche, J.; Hie, M.; Pineton De Chambrun, M.; Miyara, M.; Pha, M.; ThiHuong, D. Lê; et al.
Abstract : Background: To date, anti-dsDNA–Ab titration, better achieved with the Farr test, has been used to monitor global disease activity in systemic lupus erythematosus (SLE). Indeed, anti-DNA–Ab-positivity is associated with overall SLE activity. However, the sensitivity and specificity of that association are relatively low. The close association between Interferon alpha (IFNα) expression and SLE activity suggests that monitoring this cytokine might help physicians better evaluate disease activity. Unfortunately, no reliable simple or standardised assays to quantify IFNα are available in routine clinical practice. The new single-molecule array (Simoa) assay, also called digital ELISA, enables direct IFNα quantification at attomolar (i.e. fg/mL or 10 –15 moles/mL) concentrations corresponding to 5, 000-fold–increased sensitivity over commercial ELISAs. Objectives: We hypothesised that serum-IFNα levels determined with this new standardised assay would be a better biomarker of SLE activity than the Farr test, still considered the "gold standard" for this purpose. The primary objective of this study was to characterise the relationship between digital ELISA-determined serum-IFNα concentrations and clinically assessed SLE activity. We also compared that assay to a functional, sensitive biological assay (bioassay), based on IFNα antiviral properties, used routinely in our institution for 30 years. Methods: IFNα concentrations in serum samples from 150 consecutive SLE patients and 68 healthy donnors in a cross-sectional study were determined with the digital ELISA and the bioassay. For SLE patients, clinical characteristics, Systemic Lupus Erythematosus Disease Activity Index (SLEDAI), therapeutic regimen, Farr assay, C3 levels and other usual biological parameters were recorded on the day of the blood draw. Results: Based on healthy blood donors, the abnormal serum-IFNα level threshold value was 136 fg/mL. Next, using receiver operating characteristics curves for an SLE-patient series, widely heterogeneous for disease activity and organ involvement, the threshold IFNα value associated with active disease was 266 fg/mL. The digital ELISA-assessed serum-IFNα level was a better biomarker of disease activity than the Farr test: its specificity, positive likelihood ratio and positive-predictive value better discerned active SLE and a flare. The digital ELISA was more sensitive than the bioassay to detect low-abnormal serum-IFNα concentrations and patients with low disease activity. In multivariate analyses, abnormal digital ELISA-determined IFNα concentrations were significantly associated with SLE-specific fever, active mucocutaneous lupus, active lupus nephritis and anti-Sm Abs but no other anti-ribonucleoprotein Abs (i.e., anti-Ro/SSA 52, anti-Ro/SSA 60, anti-La/SSB and anti-RNP). Conclusions: Direct serum-IFNα determination with a highly sensitive assay might improve monitoring of clinical SLE activity and selection of the best candidates for anti-IFNα treatment. Disclosure of Interest: None declared